Efeitos da lei europeia contra desmatamento sobre as exportaç\~oes brasileiras - Marcelo José Braga Nonnenberg; Michelle Márcia Viana Martins; Alicia Cechin; Ruan da Silva Vianna; Carla Cristina Passos Cruz; Fernanda Aparecida Silva; Scarlett Queen Almeida Bispo; Francisco Santos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– Deforestation Free Products - EUDR), which aims to eliminate deforestation and forest degradation in the supply chains of agricultural products imported by the European Union (EU), on Brazilian exports of soy and beef. Deforestation, one of the main factors for greenhouse gas emissions and loss of biodiversity, is strongly linked to agricultural expansion, especially for the production of soy, beef, and other products considered forest risk by regulation. The regulation potentially affects exporting countries, especially those in Latin America and Southeast Asia, where deforestation for agricultural expansion is most prevalent. In the case of Brazil, a major exporter of soy and beef, the implementation of the EUDR could have significant implications. However, although a portion of soy and meat exports are still linked to illegal deforestation, a large part of Brazilian production complies with national environmental legislation. Furthermore, a large part of the quota exported to the EU is subject to private certifications that guarantee that the exported production is free from deforestation. To estimate the effects of the EUDR, a methodology was proposed based on the limitations of available data, to categorize municipalities and biomes according to the risk of deforestation associated with their exports. Using an indicator that considers critical municipalities, a survey was made of the potential effects of the EUDR on Brazilian soy and beef exports. The results indicate that the Cerrado and the Amazon have greater potential for lost exports, with more pronounced impacts for soy in the Cerrado and for beef in the Amazon. However, as exports to the EU are relatively low in relation to Brazil's total exports to other markets, affected exports from the Amazon was affected by a magnitude of 7% of the total, while in the Cerrado this percentage would be 3%. These values share the municipalities identified as critical in the years 2021 and 2022, as the law considers vetoing exports from suppliers who deforested as of December 31, 2020. When considering the number of critical municipalities, 480 were identified for soy and 918 municipalities for meat. The discussion of the results highlights the complexity of interactions between different links in supply chains and environmental concerns. To obtain more robust results, it is necessary to relate the agricultural input to deforestation, for this, an effort is needed in terms of traceability and field studies, to identify the routes of the products until they reach the import markets. Although Brazilian beef and soy exports to the EU do not present a high exposure in aggregate terms, certain regions and municipalities may face significant risks due to deforestation associated with the production of these goods. This will incur compliance costs to achieve due diligence requirements. The results reinforce the need for continuous efforts to improve public policies and production practices, aiming to mitigate environmental impacts and guarantee the competitiveness and sustainability of the Brazilian agricultural sector in the global market. Furthermore, in addition to analyzing the possible economic effects, the work discusses policies that could increase the value of the standing forest, reducing incentives for deforestation. European regulation is seen as an important step towards global environmental governance, but its effectiveness will depend on a joint commitment between importing and exporting countries to mitigate environmental damage.
Keywords: F1; F13; Q17; Q27; Q5; 330; EUDR; soy; beef; anti-deforestation law; environmental degradation